Soil health assessment frameworks and indicators: How can they support regeneration of smallholder farming systems in the Global South? - Pulleman, Mirjam Margreet; Bongiorno, Giulia; Visscher, Anna (2023)
Motivation, problem statement and aim: The concept of regenerative agriculture has rapidly gained momentum among agri-food companies, governments, NGO’s and farmers. Different interpretations of this concept emphasize the importance of restoring and enhancing soil health and associated ecosystem services to generate multiple benefits for society and for farmers, including productive and resilient cropping systems and landscapes and improved farmers’ livelihoods. Regenerative agriculture further seeks to mitigate greenhouse gases, thereby helping governments and agrifood companies to comply with climate mitigation targets. Conceptually, a focus on soil health, considering biological, physical and chemical aspects and multiple soil functions, has proven to be attractive for practitioners and policy makers. The popularity of the concept has thus given rise to an overwhelming demand for indicators, methods and novel technologies that can be used to assess and monitor soil health in robust and cost-effective ways. Key questions arise whether and how investments in the development and monitoring of soil health indicators support the urgently needed transition towards regenerative farms and food systems. Here, we aimed to review existing soil health frameworks and identify key challenges for their application in the context of smallholder farming in the Global South, where farmers and societies are facing the most drastic consequences of soil degradation and climate change.